THE IMPLEMENTATION OF ISLAMIC BUSINESS ETHICS IN DIGITAL MARKETING PRACTICES ON SOCIAL MEDIA - Ahmad Zaki Al-Farabi (Yayasan An-Nur Meunara Baro, 2026)
The digital landscape has witnessed a radical shift where social media platforms have become the primary marketplace. However, this transformation is often accompanied by the marginalization of ethical boundaries as brands prioritize algorithmic engagement and virality over moral integrity. In the pursuit of clicks and shares, unethical practices such as deception (gharar) and excessive exaggeration (tashni’) have become prevalent. This study aims to investigate the integration of Islamic business ethics specifically the prophetic traits of Siddiq, Amanah, Tabligh, and Fathanah into social media marketing strategies on platforms such as Instagram, TikTok, and Facebook. This research employs a qualitative approach using Netnography and Critical Discourse Analysis. The study focuses on prominent Sharia-branded business accounts as case studies, analyzing digital artifacts including video content, captions, and consumer-brand interactions in the comment sections. The results identify a significant alignment between successful ethical branding and the implementation of radical honesty in product descriptions, visual authenticity (avoiding deceptive filters), and the use of gentle communication (Qaulan Layyinan) in handling complaints. Furthermore, the study discovers the emergence of the Marketing Langit (Heavenly Marketing) model, where promotional content serves as a dual-purpose tool for commercial gain and educational dakwah. This research provides a practical and spiritual framework for Muslim entrepreneurs, demonstrating that creative digital advertising can achieve high commercial success while remaining rooted in Islamic values. By prioritizing Barakah over mere metrics, brands can foster sustainable consumer trust and contribute to a more ethical digital economy.